1990
DOI: 10.1002/j.1460-2075.1990.tb07641.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro system for the leader-primed transcription of coronavirus mRNAs.

Abstract: We have developed an in vitro transcription system which can utilize exogenous leader RNA for mouse hepatitis virus (MHV) ‘leader‐primed’ mRNA transcription. Cytoplasmic extracts containing viral proteins and template RNA were prepared by lysolecithin permeabilization of MHV‐infected cells. Synthetic leader RNA which differed in sequence from the endogenous leader RNA was added to the extracts and demonstrated to be incorporated into MHV mRNAs. Irrespective of the size of leader RNAs added, the exogenous leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 42 publications
(32 reference statements)
2
48
1
Order By: Relevance
“…This model proposes that the body TRS complement in the nascent (Ϫ) strand base pairs with the genomic (ϩ) leader TRS, thereby allowing the addition of the antileader sequence. In the alternative model of discontinuous (ϩ) strand synthesis (5,8,9,28), a 3Ј 3 5Ј exonuclease activity must be invoked (29) to explain why, after TRS base pairing, the leader TRS nucleotides are removed from the 3Ј end of the nascent sg transcript to be replaced by the complement of the (Ϫ) body TRS. Such a mechanism would be without precedent among (ϩ)RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This model proposes that the body TRS complement in the nascent (Ϫ) strand base pairs with the genomic (ϩ) leader TRS, thereby allowing the addition of the antileader sequence. In the alternative model of discontinuous (ϩ) strand synthesis (5,8,9,28), a 3Ј 3 5Ј exonuclease activity must be invoked (29) to explain why, after TRS base pairing, the leader TRS nucleotides are removed from the 3Ј end of the nascent sg transcript to be replaced by the complement of the (Ϫ) body TRS. Such a mechanism would be without precedent among (ϩ)RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The leaderprimed transcription model proposed that a free leader RNA was synthesized from the 3Ј end of the full-length minus strand. In trans, the free leader RNA binds with highly conserved internal IG elements in a full-length minus-strand template to prime transcription of each of the subgenomic mRNAs (1,3,6,19,25). More recently, it was suggested that leader body fusion might result from quasi-continuous synthesis across looped-out regions of the template which are brought together by proteinprotein interactions (22,23).…”
mentioning
confidence: 99%
“…The 3' region of leader RNA contains two or three repeats of a consensus sequence (UCUAA) complementary to negative-strand intergenic regions (Budzilowicz et al, 1985;Sheih et al, 1987). During transcription, leader RNA sequences are cleaved and fused to mRNA bodies at a junction site within the second or third (3') tandem repeat of the consensus sequence (Baker & Lai, 1990;Joo & Makino, 1992). The N protein forms high affinity complexes with the leader RNA through interaction at the 3' end of leader RNA which contains the consensus repeat S.…”
mentioning
confidence: 99%